2019
DOI: 10.1021/acs.iecr.9b02986
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical ZnO Nanotube/Graphene Oxide Nanostructures Endow Pure Zn Implant with Synergistic Bactericidal Activity and Osteogenicity

Abstract: Zinc (Zn) material has recently become a rising biodegradable metal in orthopedic applications owing to its critical physiological functions and degradation characteristics. However, the unsatisfactory cytocompatibility due to the locally high concentration of Zn ions liberated during degradation accompanied with a lack of antibacterial property and osteogenesis severely obstruct the clinical adoption of pure Zn implants. To address these challenges, we construct hierarchical ZnO nanotube/graphene oxide (GO) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…GDs could be introduced into different kinds of substrates, such as metals, [130][131][132] inorganic nonmetals, [133][134][135][136] natural polymers [137][138][139] and synthetic polymers [140][141][142][143] to prepare bone repair materials with improved performance, as shown in Table 3. In this subsection, the updated progress on research and development of those materials was reviewed.…”
Section: Composites With Different Substrates For Bone Repair Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…GDs could be introduced into different kinds of substrates, such as metals, [130][131][132] inorganic nonmetals, [133][134][135][136] natural polymers [137][138][139] and synthetic polymers [140][141][142][143] to prepare bone repair materials with improved performance, as shown in Table 3. In this subsection, the updated progress on research and development of those materials was reviewed.…”
Section: Composites With Different Substrates For Bone Repair Materialsmentioning
confidence: 99%
“…GDs played a very important role in the preparation and development of load-bearing bone materials with excellent functions. [130][131][132] Metal substrate provided hard mechanical support for load-bearing bone materials, but it also had the problems of fast corrosion rate, stress shielding and low bioactivity. Therefore, GDs with the excellent properties were used to improve the in vitro/in vivo function of the composites, and the synergistic effect of GDs and substrate provided a good microenvironment for further improving the performances of the composites.…”
Section: Composites With Different Substrates For Bone Repair Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilani et al [ 206 ] constructed ZnO micro/nano hole array and nanopariticle array on Zn foil by anodic oxidation and demonstrated superior antibacterial property against both Gram-negative E. coli and Gram-positive S. aureus . Besides, Lyu et al [ 207 ] fabricated dexamethasone-laden ZnO nanotube on Zn substrate by anodic oxidation followed by silk fibroin/graphene self-assembly. They found that this composite coating enhanced the biocompatibility and antibacterial property due to the synergistic release of Zn ions and drug during degradation.…”
Section: Surface Modification Of Zn-based Bms For Biomedical Applicationsmentioning
confidence: 99%
“…A large number of researches focus on the construction of antimicrobial coating on the surface of implant including electrochemical coating, antibiotic‐carrying polymer coating, silver‐carrying ion coating, surface antimicrobial peptide anchoring, anodic oxidation etc. [ 6–9 ] In addition, there are some studies focusing on the strategy of antibacterial modification for interbody fusion polyetheretherketone cages, such as layer‐by‐layer self‐assembly and dip‐coating methods. [ 10–11 ] However, there is few researches focused on the antibacterial modification for interbody fusion titanium (Ti) cages.…”
mentioning
confidence: 99%